Antioxidant Effect and Characterization of Metabolites in Citrullus lanatus Seed Extract (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Watermelon (Citrullus lanatus) seeds contain a complex matrix of phenolic and lipid derived metabolites capable of modulating oxidative processes at the molecular level. In this study, the antioxidant effect of C. lanatus seed extract was evaluated via in vitro and in vivo assays, and the bioactive were characterized using FTIR and GC–MS. The seeds exhibited a higher total phenolic content (584 ± 26.1 mg/g) than flavonoid content (14.04 ± 0.20 mg/g), indicating a phenolic rich antioxidant system. DPPH assays showed strong radical scavenging activity, with the aqueous fraction displaying the lowest IC₅₀ (1.65 ± 0.13 µg/mL) compared to other fractions, while total antioxidant capacity was highest in the ethyl acetate (355.50 ± 5.20 µg/mL) and n hexane (316.30 ± 0.76 µg/mL) fractions. FTIR analysis revealed characteristic O–H stretching (3286 cm⁻¹), C–H bending (1400–1346 cm⁻¹), and C–O/C–N stretching (1033 cm⁻¹), confirming the presence of alcohols, water, and complex organic functional groups associated with redox activity. GC–MS profiling of the aqueous fraction identified several antioxidant associated metabolites, including dodecanoic acid ethyl ester, decanoic acid ethyl ester, tetradecanoic acid ethyl ester, trilaurin, oleic acid (two peaks), and dodecanoic acid hydroxy ethyl ester. Evaluating the antioxidant activity in vivo demonstrated modulation of oxidative stress biomarkers, with extract treated groups showing reductions in malondialdehyde (e.g., 0.47 ± 0.085 nmol/mg at 250 mg/kg) relative to diabetic controls (0.79 ± 0.038 nmol/mg), alongside dose dependent alterations in catalase and superoxide dismutase activities. These biochemical shifts indicate attenuation of lipid peroxidation and partial restoration of endogenous antioxidant defenses. These findings demonstrate that C. lanatus seeds possess a distinct antioxidant signature driven by phenolic–lipid interactions and enzymatic modulation, supporting their relevance as a natural source of redox active compounds.
Keywords: Watermelon; Antioxidant activity; Bioactive profiling; GC-MS; Phenolics